ChemInform Abstract: Formation of Quaternary Centers by Copper‐Catalyzed Asymmetric Conjugate Addition of Alkylzirconium Reagents. Issue 51 (17th December 2013) - Sidera, Mireia; Roth, Philippe M. C.; Maksymowicz, Rebecca M.; Fletcher, Stephen P.
Abstract A new, practical, highly enantioselective, and widely applicable method to prepare cyclic ketones bearing a quaternary stereogenic center is reported.